2015
DOI: 10.1027/1866-5888/a000138
|View full text |Cite
|
Sign up to set email alerts
|

Job Crafting and Performance of Dutch and American Health Care Professionals

Abstract: Abstract. We explore how job demands and job resources are related to job crafting, and how this, in turn, is related to performance in two samples of American (US; N = 70) and Dutch (NL; N = 144) health care professionals (HCP). A cross-sectional, cross-cultural design revealed that US HCP have higher job demands and reduce them more than NL HCP, who have higher and seek more job resources. Specifically, job demands positively related to seeking resources; job resources positively related to seeking challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 48 publications
7
111
1
4
Order By: Relevance
“…Although we found only limited evidence for a link of skill variety with job crafting, other job characteristics, like autonomy, have been found to predict in particular seeking resources behaviour (in combination with work pressure; Petrou et al ., ). Furthermore, employees outside the Netherlands reported a higher tendency to reduce demands, which confirms recent findings on cultural differences in job crafting (Gordon et al ., in press).…”
Section: Resultsmentioning
confidence: 99%
“…Although we found only limited evidence for a link of skill variety with job crafting, other job characteristics, like autonomy, have been found to predict in particular seeking resources behaviour (in combination with work pressure; Petrou et al ., ). Furthermore, employees outside the Netherlands reported a higher tendency to reduce demands, which confirms recent findings on cultural differences in job crafting (Gordon et al ., in press).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this notion, Rudolph et al () found that workload, usually recognized as a “challenging demand” (that is, an obstacle to be overcome in order to learn and achieve, LePine, Podsakoff, & LePine, ), was positively related to approach crafting. Similarly, Gordon et al () found positive relationships between approach resources crafting and job demands (work pressure, cognitive demands, and emotional demands). However, Solberg and Wong () demonstrated a negative relationship between perceived role overload and approach crafting (i.e., task crafting), perhaps because role overload is one type of “hindrance demands,” which are likely to thwart personal growth and goal attainment (LePine et al, ) and thus reduce approach crafting.…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 91%
“…Although the positive effects of approach crafting and the negative effects of avoidance crafting have been supported in different cultural backgrounds, several studies have indicated that cultural differences influence individuals' job crafting behavior as well as the outcomes of job crafting. Gordon et al () compared the job crafting of health care professionals in the US (a masculine‐dominated culture) and the Netherlands (a feminine‐dominated culture), indicating that the former had higher job demands and reported more avoidance demands crafting, whereas the latter reported a higher level of approach resources crafting. Yepes‐Baldó, Romeo, Westerberg, and Nordin () found a positive linear relationship between approach crafting and psychological well‐being in a Spanish sample, but found an inverted U‐shaped curve between approach crafting and psychological well‐being in the Swedish sample.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…However, various recent studies have shown negative results of decreasing hindering job demands (e.g., Petrou et al, 2012, 2016; Tims et al, 2013; Gordon et al, 2015). Therefore, we will not include this dimension in the current study.…”
Section: Theoretical Backgroundmentioning
confidence: 99%